Mind-Independent Values Don’t Exist, But Moral Truth Does - Van Doorn, Maarten (Essays in the Philosophy of Humanism, 2017)
The falsity of moral claims is commonly deduced from two tenets: that they presuppose the existence of objective values and that these values don’t exist. Hence, the error theory concludes, moral claims are false. In this paper, I put pressure on the image of human morality that is presupposed in moving from the non-existence of objective values to the falsity of moral claims. I argue that, while, understood in a certain way, the two premises of the error theory are correct, this does not render moral discourse false, because moral objectivity is disanalogous to objectivity in empirical sciences and as such need not be characterized in terms of mind-independency. Using Dewey, I illuminate the possibility of accommodating the guiding intuitions of the error theory in a first-order account of morality.